Russian-Georgian Relations in the Captivity of the Past (History and Politics) - Keshelava, Varlam (Politics / პოლიტიკა; 2019: მესამე ნომერი, 2020)
Georgia had been the victim of the Russian aggression at different times. The same is true for the contemporary period. Russia, acting in empire spirit, aims at conquering the South Caucasus. The occupation of Abkhazia andSouth Ossetiamarked the beginning of another round of attack Georgia. The normalization of the Georgian-Russian relations and the begining of equal relations depends on the removal of the old stereotypes and will be determined by the shift in the values of the Russian citizens towards democracy, transforming society according to these principles. There is no alternative: imperial ambitions and the cult of power should be overpowered by the real practice of democratic consciousness, rather respecting it only through declarations, according to the norms of the imperial practice.